Preoperative prediction of potentially preventable morbidity after fast-track hip and knee arthroplasty: a detailed descriptive cohort study. Issue 1 (12th January 2016) - Jørgensen, Christoffer C; Petersen, Morten Aa; Kehlet, Henrik
Abstract : Objectives: Construction of a simple preoperative risk score for patients in high risk of potentially preventable 'medical' complications. Secondary objectives were to construct simple preoperative risk scores for 'severe medical', 'surgical' and 'total' potentially preventable complications. Design: Prospective observational study. Setting: Elective primary unilateral total hip and knee arthroplasty with prospectively collected preoperative patient characteristics; similar standardised fast-track protocols; evaluation of complications through discharge and medical records; and complete 90 days follow-up through nationwide databases. Participants: 8373 consecutive unselected total hip arthroplasty (THA) and knee arthroplasty from January 2010 to November 2012. Results: There were 557 procedures (6.4%) followed by potentially preventable complications resulting in hospitalisation >4 days or readmission. Of 22 preoperative characteristics, 7 were associated with 379 (4.2%) potentially preventable 'medical' complications. Patients with ≥2 of the following, age ≥80 years, anticoagulant therapy, pulmonary disease, pharmacologically treated psychiatric disorder, anaemia and walking aids, composed 19.1% of the procedures; 55.7% constituted potentially preventable 'medical' complications that were mainly falls, mobilisation issues, pneumonias and cardiac arrhythmias. The number needed to be treated for a hypothetical intervention leading to 25% reduction in potentially preventable 'medical' complications was 34. THA, use of walking aids and cardiac disease were associated with 189 (2.2%) 'surgical' complications, but no clinically relevant preoperative prediction was possible. Conclusions: Preoperative identification of patients at high risk of preventable 'medical', but not 'surgical', complications is statistically possible. However, clinical relevance is limited. Future risk indices should differ between 'medical' and 'surgical' complications, and also consider 'preventability' of these. Trial registration number: NCT01515670.